Molecular Characterization of Anisakis spp.: Potential Source of Fish-borne Zoonosis in Coastal Living Environment in Semarang, Indonesia - Hitipeuw, Derico; Daud, Muhammad Muzhaffar; Nuranindita, Raisha; Diyana, Sutra; Amirudin, Fariha Akmalina; Rahayu, Aprillia Andika; Saputra, Edo Yungki; Qanita, Nabila Gusvie; Natanegara, Surya; Yuwanita, Mutiara Rizqi; Wusono, Ajeng Dwi; Martini, Martini; Muh, Fauzi (HAYATI Journal of Biosciences, 2026)
Anisakis spp. are marine nematodes known to cause anisakiasis, a zoonotic disease transmitted through fish consumption with diverse clinical manifestations. In Indonesia, a country with extensive marine biodiversity and high fish consumption, data on anisakiasis remain limited. This study aimed to characterize the Anisakis spp. from the most significant commercial fish market in Semarang, Indonesia. A total of 17 Rastrelliger sp. were sampled. PCR amplification targeting the mitochondrial COX2 gene was used to identify the species of Anisakis spp. molecularly. Phylogenetic relationships, nucleotide diversity, and neutrality indices were assessed. The haplotype structures were visualized using the Haplotype Network. Subsequently, 7 of 17 (41.17%)  Rastrelliger sp. samples were infected with A. typica. Molecular analysis revealed two species, A. typica and H. amoyense, with high haplotype diversity (1.00±0.016, diversity±SD). Phylogenetic analysis revealed two major clades: A. typica (Semarang and Southern Makassar) and H. amoyense (Semarang, China, and Bangladesh), with both species indicating high genetic connectivity. Neutrality indices suggested purifying selection and population expansion for both species (dN-dS = -5.017). These findings highlight the genetic variability and zoonotic potential of Anisakis spp. in the commercial fish market, emphasizing the need for surveillance of fish-borne parasitic infections in Indonesia.